Implementation of Quantum Teaching Model On Improving Physics Learning Outcomes In The Cognitive Domain At Junior High School - Fayanto, Suritno; Musria, Musria; Erniwati, Erniwati; Sukariasih, Luh; Hunaidah, Hunaidah (IJIS Edu : Indonesian Journal of Integrated Science Education, 2019)
Teaching physics must present as attractive as possible students can identify, search, and formulate problems, and able to solve issues in detail. This study aims to describe the improvement of learning outcomes in physics-cognitive realm using quantum teaching model. The location of the study place at junior high school 1 Lohia, Muna Regency, Indonesia. The study sample consisted of 22 students of junior high school class VIII2 studied through a quantum teaching model, and 22 VIII3 junior high school students learned conventional learning models from a population of 88 people. The subject matter used to wave and vibration. This type of research classroom experiment research using a pretest-posttest control group design. Data collection techniques used tests of cognitive learning outcomes of students in the form of multiple choices. The analysis technique uses descriptive and inferential analysis. The final results conclude the average value of the final test of students on the learning outcomes of the learning knowledge of students through the quantum teaching model is higher than the average value of the final test of students learn through conventional learning models based on a significance value of 0.029